Principal's Leadership Style in Increasing School Committee Participation - Slamet Riyadi (Universitas Islam Negeri Sumatera Utara Medan, 2019)
AbstractThe school principal was instrumental in optimizing the function of the schoolcommittee in advancing the school he leads, the role of the school committee isrequired in advancing education, school principals must have a style ofleadership to enable the duties and responsibilities of school committees forthe schools into schools that are reliable and qualified, disciplined, Science andtechnology and devoted to God Almighty.